The Electronic Class Record Used by The Cavite State University-Naic Faculty: Its Prospects - Gutierrez, Ernesto A. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
The study was conducted at the Cavite State University-Naic. It aimed to assess the existing electronic class record (e-class record) used by the faculty members, problems encountered by teachers on the use of e-class record; and recommend solutions for teachers and administrators to solve problems encountered in the use of e-class record. The statistics used were weighted mean, ranking, frequency distribution, and percentile. In the assessment, faculty members believed that using the electronic class record lessens the amount of time spent by teachers in grade computation. They also believed that the e-class record made their computation easier with a weighted mean of 4.62. All faculty members favored the benefits of using the electronic class record. Meanwhile, the lowest mean of 3.79 is on the use of electronic class records to help update students about their academic strengths and weaknesses. Most of the recommended solutions in the survey were agreed upon by the teachers. First on the rank was that there should be an immediate response from technical personnel regarding problems with the computer system. The second was the conduct of regular updates of the e-class record. The third was to provide adequate computer facilities such as printers and computers for the faculty to encode their grades. And last on the recommendation was the conduct of training on basic computer skills.